2020
DOI: 10.1002/hbm.25323
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging improves brain age prediction and reveals distinct abnormalities in patients with psychiatric and neurological disorders

Abstract: The deviation between chronological age and age predicted using brain MRI is a putative marker of overall brain health. Age prediction based on structural MRI data shows high accuracy in common brain disorders. However, brain aging is complex and heterogenous, both in terms of individual differences and the underlying biological processes. Here, we implemented a multimodal model to estimate brain age using different combinations of cortical area, thickness and sub‐cortical volumes, cortical and subcortical T1/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
89
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 86 publications
10
89
0
Order By: Relevance
“…Relative to more traditional MRI summary measures, age prediction models have the advantage of encoding normative trajectories of brain differences across age, and condensing a rich variety of brain characteristics into single estimates per individual. Hence, brain age prediction provides a useful summary measure that may serve as a proxy for brain integrity across normative and clinical populations (Cole & Franke, 2017 ; Cole, Marioni, et al, 2019 ; Kaufmann et al, 2019 ; Rokicki et al, 2020 ; Smith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to more traditional MRI summary measures, age prediction models have the advantage of encoding normative trajectories of brain differences across age, and condensing a rich variety of brain characteristics into single estimates per individual. Hence, brain age prediction provides a useful summary measure that may serve as a proxy for brain integrity across normative and clinical populations (Cole & Franke, 2017 ; Cole, Marioni, et al, 2019 ; Kaufmann et al, 2019 ; Rokicki et al, 2020 ; Smith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…2018 ; Liang et al. 2019 ; Rokicki et al. 2020 ), although there might be other underlying explanations as well, for example, a nonlinear relationship between age and brain measures that would be more effectively captured using a nonlinear modeling approach.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of these previous studies have demonstrated better results when including multimodal neuroimaging data rather than a single modality in the models 22 , 26 , 27 . In particular, findings from these multimodality studies suggest that dMRI measures have higher accuracy in predicting brain age compared to those derived from fMRI, SWI or even anatomical images in some cases 1 , 11 .…”
Section: Introductionmentioning
confidence: 99%